The Effect of Think Pair Check Model on Students Understanding of Mathematical Concepts in Terms of Cognitive Style - Yerizon Yerizon; Farhani Farhani; Hendra Syarifuddin; Nor’ain Mohd Tajudin (Universitas Syiah Kuala, 2020)
This quasi-experimental research aims to determine the effect of Think Pair Check (TPC) learning models on understanding of mathematical concepts in terms of cognitive style. A purposive sampling technique was used to select a sample of 54 students from a junior high school in Patamuan sub-district, Indonesia. The data were obtained from mathematical concept understanding tests and Group Embedded Figure Test (GEFT) to determine students' cognitive styles. Data were analyzed using t-test. The findings indicated that students who learned using TPC method had a better understanding of concepts than those learning using the conventional model. Furthermore, the TPC learning model positively influenced the understanding of mathematical concepts of students with the Field Independent cognitive style but had no influence on students with the Field Dependent cognitive style. Therefore, the TPC learning model can be used to improve the understanding of mathematical concepts, especially for students with the Field Independent cognitive style.